Frictional Security Governance: policing the Crime-Terror Nexus in Denmark - Johansen, Mette-Louise (Perspectives on terrorism, 2021)
This article examines policy responses to crime and terror as cases through which to illuminate the transformations of contemporary security governance in Denmark. The policies reveal how particular events have triggered a process of security escalation in which conflated notions of threat have called for new policing measures and organizations. We focus on three critical events linked to ‘foreign fighters’, ‘gangs’, and ‘crossovers’ as cases of escalating threat through which to analyze the expansion and conflation of security domains. Policy responses to the crime-terror nexus, we argue, merge reactive and proactive policing measures and formerly distinct domains of securitization and risk management, highlighting the frictional characteristics of security governance. While the Danish Model—informed by a networked-based and multiagency approach to preventing and countering radicalization and extremism—is often referred to as a model of best practice—we propose that future research needs to explore in greater detail how the expansion and conflation of security domains impact security actors who are mandated to implement the operational response to crime and terror.